Fast specific field detection of RHDVb. Issue 1 (28th February 2017) - Dalton, K. P.; Nicieza, I.; Podadera, A.; de Llano, D.; Martin Alonso, J. M.; de los Toyos, J. R.; García Ocaña, M.; Vázquez‐Villa, F.; Velasco, B.; Landeta, O.; Parra, F.
Summary: This work describes a simple and rapid test for field detection of the emerging rabbit pathogen RHDVb. The assay is specific for RHDVb, showing no cross‐reactivity with other RHDV types giving a specific result in under 10 min using rabbit liquid exudates or liver homogenate samples taken at necropsy.